Fabricating 'Economic development' - Brownlow, Graham (Economic & Social Studies, 2010)
Much of the literature, regardless of academic discipline, presents the publication of Economic Development in 1958 as analogous to a ?big bang? event in the creation of modern Ireland. However, such a ?big bang? perspective misrepresents the sophistication of economic debates prior to Whitaker?s report as well as distorting the interpretation of subsequent developments. This paper reappraises Irish economic thinking before and after the publication of Economic Development. It is argued that an economically ?liberal? approach to Keynesianism, such as that favoured by T. K. Whitaker and George O?Brien, lost out in the 1960s to a more interventionist approach: only later did a more liberal approach to macroeconomic policy triumph. The rival approaches to academic economics were in turn linked to wider debates on the influence of religious authorities on Irish higher education. Academic economists were particularly concerned with preserving their intellectual independence and how a shift to planning would keep decisions on resource allocation out of the reach of conservative political and religious leaders.
Keywords: Economists; Historiography; Ireland; Economic development